THE ROLE OF DIGITAL COMMUNICATION IN REBRANDING THE IMAGE OF PT. ANGKASA PURA INDONESIA IN SOCIAL AND RELIGIOUS PERSPECTIVES - Julianta Pratama Pinem; Isnaini, Muhamad; Menayang, Alfred P. (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This study examines the role of digital communication in the image rebranding process of PT. Angkasa Pura Indonesia, using a social and religious perspective. With the development of information technology and changing public expectations, companies are required to transform their identities through adaptive and valuable communication strategies. Digital communication has become a primary means of rebuilding a company's image by delivering messages that are more inclusive, interactive, and nuanced with social and religious values. In this context, digital media such as official websites, social media, and other digital platforms are used to instill the values of humanistic, transparent public service, reflecting local wisdom and a spirit of interfaith tolerance. This study uses a qualitative approach with descriptive analytical methods, focusing on how digital communication messages are structured and delivered by the company within the framework of its rebranding. The analysis shows that digital communication serves not only as a visual promotional tool but also as a dialogue space that enables the formation of new, positive perceptions of the company, particularly regarding social responsibility, service ethics, and respect for the cultural and religious diversity of airport users. Thus, rebranding through digital communication is a strategy that is not only aesthetic but also ethical and humanistic, in line with the socio-religious values prevailing in Indonesian society.